Ta, ta, ta, que los gallos no cantan: música i intertextualitat en contrafacta austriacistes durant la guerra de Successió. - PLANAGUMÀ-CLARÀ, LAURA (Scripta, 2023)
The War of the Spanish Succession was a military conflict, but also a propagandistic one. Between writing and orality, one of the most effective forms of propagation of political messages were the contrafacta, texts designed to be sung with pre-existing melodies. These circulated printed on single-sheet broadsides or small, book-like pamphlets, but only the texts were reproduced on these physical objects; the widely known tunes with which they were sung were not copied, but only the name was indicated by expressions such as «to the tune of». Although at the time these tune names evoked a whole sonic and conceptual context, today we have lost the referents. In this article, we study seven contrafacta that circulated between 1705 and around 1706, the height of Austrian propaganda. On the one hand, we study the possible intertextual processes involved in these contrafacta, implicit by their very nature as a product of literary and musical reuse. On the other hand, we tackle the musical recreation of these pieces that were intended to be sung. This will allow us to gain an in-depth knowledge of each of these songs, which reveals in detail some of the propaganda mechanisms adopted by Austriacists side in the conflict.